Educação matemática através de interfaces computacionais: o papel de componentes interativos na postura exploratória e na aprendizagem - PEREIRA FILHO, Silvio Carlos Ferreira (Universidade Federal do Pará, 2012)
In this work, we investigate the role of interactive components frequently used at educational computer-interfaces design at the exploratory posture and learning mathematics concepts. We selected two components in this research: combo box and text field. From educational perspective these components have distinct role: the former guides the student's choices in exploratory process, the second don’t offer any guidance. In order to compare the role of these components, we have built two interactive interfaces, used by students to explore the graphical behavior of the linear function. Both interfaces are identical except for the components (combo box and field text). The exploratory posture and performance on knowledge test were assessed through data collected by the own interfaces. The exploratory posture was assessed through amount and exploration type with interactive component, this collect was a unique feature of this research allowing us to observe student’s behavior while interactive process instead of before and after interaction. Due the limitation of the tool used to collect data in this research, learning was measured by comparison of performance on knowledge tests applied before and after student’s uses of interactive components. In this context we noticed significant differences at the exploratory posture and development among students in two groups, each one using one kind of interactive component.